Impaired high-density lipoprotein function and endothelial barrier stability in severe anaphylaxis - Fernández Bravo, Sergio; Canyelles, Marina; Martín Blázquez, Ariadna; Borrás, Carla; Núñez Borque, Emilio; Palacio García, Lucia; Rodríguez del Rio, Pablo; Betancor, Diana; Gómez López, Alicia; Sabaté Brescó, Marina; Laguna Martínez, Jose Julio; Méndez Barbero, Nerea; et al. (My University, 2024)
Background: Growing evidence demonstrates the importance of high- and low-density lipoprotein cholesterol in certain immune and allergy-mediated diseases. Objective: This study aimed to evaluate levels of high- and low density lipoprotein cholesterol and apolipoproteins A1 and B in sera from a cohort of patients presenting with hypersensitivity reactions. We further assessed the function of high-density lipoprotein particles as well as their involvement in the molecular mechanisms of anaphylaxis. Methods: Lipid profile determination was performed in paired (acute and baseline) serum samples from 153 patients. Thirty eight experienced a non-anaphylactic reaction and 115 had an anaphylactic reaction (88 moderate and 27 severe). Lecithin cholesterol acyl transferase activity was assessed in patient sera, and we also evaluated macrophage cholesterol efflux in response to the serum samples. Last, the effect of anaphylactic-derived high-density lipoprotein (HDL) particles on the endothelial barrier was studied. Detailed methods are provided in the Methods section in this article¿s Online Repository available at www.jacionline.org. Results: Serum samples from severe anaphylactic reactions show statistically significant low levels of HDL cholesterol, low-density lipoprotein cholesterol, and apolipoproteins A1 and B, which points to their possible role as biomarkers. Specifically, HDL particles play a protective role in cardiovascular diseases. Using functional human serum cell assays, we observed impaired capacity of apolipoprotein B¿ depleted serum to induce macrophage cholesterol efflux in severe anaphylactic reactions. In addition, purified HDL particles from human anaphylactic sera failed to stabilize and maintain the endothelial barrier. Conclusion: These results encourage further research on HDL functions in severe anaphylaxis, which may lead to new diagnostic and therapeutic strategies. (J Allergy Clin Immunol 2024;154:827-32.) Key words: Anaphylaxis, high-density lipoprotein cholesterol, macrophage cholesterol efflux, vascular permeability
Keywords: Anaphylaxis, high-density lipoprotein cholesterol, macrophage cholesterol efflux, vascular permeability